ANALISIS SWOT TRANSFORMASI KELEMBAGAAN STAI AL-MASTHURIYAH SUKABUMI MENUJU INSTITUT - Ashima Ailya; Rike Junia Ningarumsari; Teti Ratnawulan; Lilis Suwandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Institutional transformation in higher education has become a strategic necessity to improve governance quality, academic capacity, and institutional competitiveness. However, empirically, STAI Al-Masthuriyah Sukabumi still faces various challenges in its implementation. This study aims to describe and analyze the internal and external factors influencing the transformation process through the mapping of strengths, weaknesses, opportunities, and threats. The study employs Lewin’s Institutional Transformation Theory, Albert Humphrey’s SWOT Analysis in Strategic Management, and Kezar’s Higher Education Management Theory as theoretical frameworks. A descriptive qualitative approach was applied through observation, in-depth interviews, and document studies involving institutional leaders, lecturers, educational staff, and relevant stakeholders. The results indicate that STAI Al-Masthuriyah possesses strengths in its pesantren-based identity and strong social support but still faces weaknesses in digital governance and unequal human resource competencies. The main opportunities come from government policies and the growing public interest in Islamic education, while threats arise from changes in the accreditation system and increasing competition among Islamic higher education institutions (PTKIS). The institutional transformation process proceeds through human resource development, curriculum renewal, the establishment of new study programs, and the gradual and collaborative digitalization of academic administration.